2012
DOI: 10.15288/jsad.2012.73.303
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Supervisor Social Control to Employee Substance Use: Considering the Dimensionality of Social Control, Temporal Context of Substance Use, and Substance Legality

Abstract: ABSTRACT. Objective: Research on supervisor social control provided little evidence for a relation to employee alcohol use, and only one study explored illicit drug use. Based on past research, several hypotheses were developed that the relation between supervisor social control and substance use depends on (a) the dimension social control (contact vs. enforcement), (b) the temporal context of substance use (on the job vs. off the job), and (c) substance legality (alcohol vs. illicit drugs). Method: Data came … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
8
1
1
Order By: Relevance
“…However, only work fatigue conditionally mediated the relation of work stressor exposure to workday alcohol use and only negative affect conditionally mediated the relation of work stressor exposure to after work alcohol use. These differential effects support prior research showing that other workplace predictors, such as supervisor social control (Frone & Trinidad, 2012) and workplace alcohol use norms (Frone & Brown, 2010) show differential relations across alcohol use outcomes. Even if differential relations are not expected or observed, using a broad set of alcohol outcomes provides evidence that a given feature of the workplace has a consistent impact on employee alcohol use.…”
Section: Discussionsupporting
confidence: 84%
“…However, only work fatigue conditionally mediated the relation of work stressor exposure to workday alcohol use and only negative affect conditionally mediated the relation of work stressor exposure to after work alcohol use. These differential effects support prior research showing that other workplace predictors, such as supervisor social control (Frone & Trinidad, 2012) and workplace alcohol use norms (Frone & Brown, 2010) show differential relations across alcohol use outcomes. Even if differential relations are not expected or observed, using a broad set of alcohol outcomes provides evidence that a given feature of the workplace has a consistent impact on employee alcohol use.…”
Section: Discussionsupporting
confidence: 84%
“…To the extent that work demands increased among those who retained employment and the available labor force increased with downsizing, employers may have been more likely to monitor employee work behavior and employees may have been more sensitive to this possibility leading to elevated levels of job insecurity. Also, because alcohol use is legal, employer substance use policies generally proscribe alcohol use during the workday, but do not address alcohol use outside work, such as after-work use (Frone & Trinidad, 2012). Therefore, based on these arguments and self-medication models of stress-induced alcohol use, it is hypothesized that the Great Recession will be associated with a decrease in alcohol use during the workday to avoid job loss and an increase in alcohol use after work to reduce stress.…”
Section: The Present Studymentioning
confidence: 99%
“…In contrast, findings with regard to the impact of supervisor contact and monitoring/enforcement are equivocal with protective (i.e., negative) effects found in some studies (e.g., Ames et al, 2000;Frone & Trinidad, 2012) and null effects found in others (Bacharach et al, 2002;Macdonald, Wells, & Wild, 1999). For example, Frone and Trinidad (2012) found supervisory enforcement to be negatively associated with employee alcohol consumption at work, and Ames et al (2000) found ethnographic evidence that employee perceptions of their supervisor's willingness and ability to intervene in suspected cases of employee alcohol impairment at work was negatively associated with problem drinking. In contrast, when controlling for other risk factors, Bacharach et al (2002) found supervisory willingness and ability to intervene to have no significant link with employee problem drinking.…”
Section: Workplace Social Control and Policy Enforcementmentioning
confidence: 92%